2010
DOI: 10.3899/jrheum.100482
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Cost and Loss of Productivity in a Canadian Population of Patients with and without Lupus Nephritis

Abstract: Healthcare cost and loss of productivity were similar between patients with LN and patients who were LNN; the loss of productivity for caregivers is higher for patients with LN; and the healthcare cost is greater in ALN than in ILN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 35 publications
3
37
1
1
Order By: Relevance
“…Substantial levels of inpatient care, medication/prescriptions and visits to healthcare professionals (HCP), which are all increased by ‘flares’, are the main drivers of direct costs in the treatment of SLE [43]. The conceptual model also shows that SLE is associated with high indirect costs due to lost productivity [5] resulting from unemployment and absenteeism, [44], with ‘in-flare’ patients with SLE having increased frequency and duration of time off work [45],[46]. …”
Section: Resultsmentioning
confidence: 99%
“…Substantial levels of inpatient care, medication/prescriptions and visits to healthcare professionals (HCP), which are all increased by ‘flares’, are the main drivers of direct costs in the treatment of SLE [43]. The conceptual model also shows that SLE is associated with high indirect costs due to lost productivity [5] resulting from unemployment and absenteeism, [44], with ‘in-flare’ patients with SLE having increased frequency and duration of time off work [45],[46]. …”
Section: Resultsmentioning
confidence: 99%
“…Systemic autoimmune rheumatic diseases (SARDs) are complex chronic inflammatory disorders (such as systemic lupus, SLE) characterized by multi-system inflammation 1-3 and high disease burden. 4 Although there is some evidence that SARDs may be triggered by environmental factors 5-8 there remain considerable knowledge gaps regarding mechanisms through which the environment may trigger these autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated the costs and resource utilization associated with lupus nephritis and NPSLE in a US insurance claims database. While a few studies have reported on costs associated with lupus nephritis [10][11][12][13][14] , little data exist on costs and resource use associated with NPSLE 15 . To ensure that results from this study would be representative of all stages of disease (and not just the initial stage), we used a prevalent approach to identify subjects.…”
mentioning
confidence: 97%